The Analysis of Factors Influencing Stunting Prevention Behavior in Pregnant Women - Ika Sumiyarsi Sukamto; Dian Nintyasari Mustika; Septiana Juwita (Journal of Health Promotion and Behavior, 2025)
Background: Stunting is a serious health issue in Indonesia, impacting children's growth and development due to chronic malnutrition, recurrent infections, and harmful environmental factors. This study aimed to examine factors influencing stunting prevention behavior in pregnant women Subjects and Method: A quantitative study with a path analysis approach. It was conducted in Probolinggo Regency using cluster random samping, based on inclusion criteria. The sample size consisted of 220 respondents spread across four community health centers (Puskesmas). The research variables include independent varaibles: exposure to cigarette smoke, socio-economic status, and social support; intervening variables: acces to healthcare services and health status; and dependent variable: stunting prevention behavior. The research instrument useda questionnaire based on the theoryof factors influencing stunting prevention in pregnant women, Data analysis was performed using path analysis with Amos software. Results: Social support on stunting prevention behavior through health status of pregnant women (Z-value = 1.23; p-value = 0.022). Social support on stunting prevention behavior in pregnant women through access to healthcare services (Z-value = -3.92; p-value = 0.00). Cigarette smoke exposure on stunting prevention behavior through health status of pregnant women (Z-value = 10.53; p-value = 0.00). Socio-economic status on stunting prevention behavior through health status of pregnant women (Z-value = 2.19; p-value = 0.03). Conclusion: Health promotion targeting the improvement of socio-economic status and social support, as well as preventing tobacco smoke exposure, plays a significant role in influencing stunting prevention behavior among pregnant women. Health status and access to healthcare services act as mediators that link social support, tobacco smoke exposure, and socio-economic status to stunting prevention behavior. By implementing community-based health promotion strategies, we can prevent stunting in a more holistic and sustainable manner.